Part I: Intermolecular hydroamination between nonactivated alkenes and aniline catalyzed by lanthanide salts in ionic solvents. Part II: NHC-Pd complex catalyzed allylic amination using ammonia for the synthesis of primary amines - Yin, Peng (2012)
The catalytic hydroamination of alkenes provides an efficient and direct entry to synthetically useful amines. An efficient method for the hydroamination between non-activated alkenes and aniline catalyzed by the system of Pr(OTf)3/n-Bu4PI/I2 was developed. Allylamines are important building blocks in organic synthesis, and are also used as starting materials for the synthesis of many compounds such as amino acids, and different alkaloids. Two catalytic systems for the allylic amination with aqueous ammonia and ammonia gas were well-developed.